Family Communication Between Single Father And Daughter In Affection Exchange - Monica Tyas Cahya Deivita (Lingkar Studi Komunikasi (LISKI), 2023)
The phenomenon of single fathers experiencing divorce and death has its own challenges in carrying out duties and responsibilities as parents, especially in taking care of adolescent girls, in which case adolescence is a transitional period towards adulthood so communication of affection is needed within the family. Researchers focused on families of single fathers and adolescent girls in the Special Region of Yogyakarta. This study uses a naturalistic paradigm. The data obtained in this study were obtained through observation, in-depth interviews, and documentation from the six key informants, namely single fathers and adolescent daughters, two supporting informants, and one expert informant. In this study, researchers found that family communication affects the form of messages that are produced in a form of exchange of affection, which can be in the form of verbal communication and nonverbal communication in relation to the exchange of affection and parenting patterns of single fathers. In addition, single fathers who communicate affection with their children have lower levels of stress and conflict avoidance than single fathers who do not communicate affection with their children. Therefore, affectionate communication contributes to the family because it can minimize conflicts that may occur between single fathers and adolescent girls. Keywords: Affection Exchange, Family Communication, Single Father, Adolescent Girls